Fatty acid composition of Mediterranean buffalo milk fat - V. Proto; F. Masucci; R. Romano; A. Di Francia; M. L. Varricchio (Italian Journal of Animal Science, 2010)
The purpose of this research was to investigate the variation in fatty acid composition of milk fat from four buffalo (Bubalus bubalis) herds under different feeding management and ration composition. Changes in milk fatty acid composition were monitored on a weekly basis. Saturated fatty acids (65.5%) predominated in buffalo milk fat; monounsaturated and polyunsaturated fatty acids were 27.0% and 4.5%, respectively. Of saturated fatty acids, the content of palmitic acid was the highest (30.6%) followed by stearic acid (12.0%) and myristic acid (10.7%). Of the unsaturated fatty acids the content of oleic acid was the highest (26.6%). The average content of conjugated linoleic acid (0.76±0.33) was higher than the maximal values generally reported for dairy cow.